2011
DOI: 10.1111/j.1439-0272.2011.01190.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of red maca (Lepidium meyenii) on prostate zinc levels in rats with testosterone-induced prostatic hyperplasia

Abstract: Lepidium meyenii (maca) is a plant that grows exclusively above 4000 m in the Peruvian central Andes. Red maca (RM) extract significantly reduced prostate size in rats with benign prostatic hyperplasia (BPH) induced by testosterone enanthate (TE). Zinc is an important regulator of prostate function. This study aimed to determine the effect of RM on prostate zinc levels in rats with BPH induced by TE. Also, the study attempted to determine the best marker for the effect of RM on sex accessory glands. Rats treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
3
19
0
1
Order By: Relevance
“…La maca roja reduce los niveles de zinc intraprostático (incrementados en HPB) cuando es administrada del día 1 al día 14 teniendo en cuenta que el enantato de testosterona es aplicado el día 1 y el día 7 (69) . En la actualidad es importante realizar un ensayo clínico en pacientes que sufren de HBP para poder determinar su eficacia en seres humanos.…”
Section: Maca E Hiperplasia Benigna De Próstataunclassified
“…La maca roja reduce los niveles de zinc intraprostático (incrementados en HPB) cuando es administrada del día 1 al día 14 teniendo en cuenta que el enantato de testosterona es aplicado el día 1 y el día 7 (69) . En la actualidad es importante realizar un ensayo clínico en pacientes que sufren de HBP para poder determinar su eficacia en seres humanos.…”
Section: Maca E Hiperplasia Benigna De Próstataunclassified
“…In accordance with this assumption, previous phytochemical screening of the red Maca aqueous extract has shown presence of glucosinolates and anthocyanins (Fahey, Zalcmann, & Talalay, 2001;Li et al, 2001) which could exert antiproliferative and proapoptotic activity on various models of human prostate cancer (Chiao et al, 2004;Le et al, 2003;Shapiro, Fahey, Wade, Stephenson, & Talalay, 1998;Wong et al, 2014). Furthermore, red Maca aqueous extract has antihyperplastic effects on the prostate of adult rodents (Gonzales et al, 2008(Gonzales et al, , 2012. In contrast, our results showed that treatment with red Maca aqueous extract did not affect viability nor exerted coadjutant effect to Taxol or 2ME in LNCaP cells, suggesting that this type of extract is not toxic for human prostate cancer cell lines.…”
Section: Discussionmentioning
confidence: 71%
“…Administration of red Maca aqueous extract attenuated prostate hyperplasia in rodent models (Gonzales, Gasco, Malheiros-Pereira, & Gonzales-Castañeda, 2008;Gonzales, Leiva-Revilla, Rubio, Gasco, & Gonzales, 2012). Furthermore, there are data relating Maca consumption to enhanced sexual desire, fertility and spermatogenesis (Cicero, Bandieri, & Arletti, 2001;Milligan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…[21] It is known that estradiol acts synergistically with androgens to cause overgrowth of the prostate. [2] Etiopathological mechanism consists of control of endocrine processes and alterations in the balance between androgens and estrogens.…”
Section: Discussionmentioning
confidence: 99%